Anxiety Body Odors as Context for Dynamic Faces: Categorization and Psychophysiological Biases. (October 2018) - Rocha, Marta; Parma, Valentina; Lundström, Johan N.; Soares, Sandra C.
Body odors (BOs) can convey social information. In particular, their effects are maximal when their presence is paired with meaningful social contexts. Static faces have been widely used as social stimuli. However, they miss a key feature of our phenomenological experience, characterized by multisensory dynamic stimulations. Here, we investigate how BO sampled from individuals experiencing a transitory anxiety state, (a) induce a stress response and (b) bias the recognition of dynamic facial expressions, compared with BO of relaxed individuals. Participants ( n =46) categorized the emotion of a face, morphing from a neutral expression to either an angry or happy expression, during exposure to either BO condition. In addition, their cardiac activity was measured. Exposure to anxiety BO increased the accuracy of dynamic facial recognition and reduced cardiac parasympathetic activity. These results suggest that in social situations that simulate part of the multisensory and dynamic features of real-life social contexts, anxiety BOs will induce a stress response in recipients, modulating both arousal and cognitive-emotional skills but facilitating emotional facial processing.